Analysis of differences in intesity and movement quantity between center and guard during the water polo game - Lozovina, M. (Sport Science - International Scientific Journal of Kinesiology, 2021)
On the representative sample of 360 water polo quarters that represent entities, 21 originally measured variables were applied and 8 of them derived. Based on the primary analysis of the central and dispersion parameters of all the variables, for the final analysis eleven varables were left, that had normal or approximate normal distribution. The aim of this paper was to determine whether in the structure of motion in the vertical and horizontal phase of the game during a water polo match in situ conditions regarding to modes, intensities, frequencies and time as the determinants of the load equivalent in the game, can be established and analyzed the differences between players performing various tasks , defined by the role of the center and the guard. For this purpose, statistics of all variables were calculated, variance analysis (ANOVA) was performed. The canonical discriminatory analysis was performed, the positions of the centroids for both groups and the structure of the discriminatory function were calculated. The obtained results suggest that it is possible to register and identify the differences in the game of center and guard in water polo, by measuring in situational conditions, which is also a confirmation of the aim of research set in this paper. The results obtained, except for contributing to the theoretical explanation of this otherwise less elaborate area in top sports, will be the basis for a practical approach to water polo coaches working with centers and guards.